Colonization and genetic diversification processes of Leishmania infantum in the Americas - Schwabl, Philipp; Boité, Mariana C; Bussotti, Giovanni; Jacobs, Arne; Andersson, Bjorn; Moreira, Otacilio; Freitas-Mesquita, Anita L; Meyer-Fernandes, Jose Roberto; Telleria, Erich L; Traub-Csekö, Yara; Vaselek, Slavica; Leštinová, Tereza; et al. (Communications biology, 2021)
Leishmania infantum causes visceral leishmaniasis, a deadly vector-borne disease introduced to the Americas during the colonial era. This non-native trypanosomatid parasite has since established widespread transmission cycles using alternative vectors, and human infection has become a significant concern to public health, especially in Brazil. A multi-kilobase deletion was recently detected in Brazilian L. infantum genomes and is suggested to reduce susceptibility to the anti-leishmanial drug miltefosine. We show that deletion-carrying strains occur in at least 15 Brazilian states and describe diversity patterns suggesting that these derive from common ancestral mutants rather than from recurrent independent mutation events. We also show that the deleted locus and associated enzymatic activity is restored by hybridization with non-deletion type strains. Genetic exchange appears common in areas of secondary contact but also among closely related parasites. We examine demographic and ecological scenarios underlying this complex L. infantum population structure and discuss implications for disease control.
Keywords: molekulární evoluce; Genome, Protozoan; Phylogeny; Evolution, Molecular; protozoální DNA; Molecular Epidemiology; Brazílie; Whole Genome Sequencing; protozoální geny; Genes, Protozoan; DNA, Protozoan; Sequence Deletion; molekulární epidemiologie; sekvenování celého genomu; delece genu; Gene Deletion; sekvenční delece; fylogeneze; Brazil; leishmanióza viscerální; Leishmania infantum; Leishmaniasis, Visceral; genom protozoální